Hubungan Tingkat Stress Dengan Kadar Gula Darah Pada Pasien Diabetes Mellitus di Puskesmas Simpang IV Sipin - Putra, Dimas Hendri; Oktarina, Yosi; Sulistiawan, Andika (Jurnal Ilmiah Dikdaya, 2023)
Diabetes Mellitus is a chronic disease characterized by an increase in blood glucose. The International Diabetes Federation predicts that by 2045 there will be an increase in diabetes cases of 700 million in the world. The increase in diabetes cases is closely related to the therapeutic process in patients, the process results in emotional distress until patients experience stress. Stress in diabetes has an impact on unstable blood sugar control due to increased glucose levels in the blood. So a study was conducted to determine the relationship between stress and blood sugar levels in Diabetes Mellitus patients. Research using quantitative methods with a cross sectional approach. The study population of 291 obtained 80 samples using purposive sampling techniques. The research media were DDS (Diabetes Distress Scale) questionnaire and glucometer. Univariate data analysis using frequency distribution. Bivariate data analysis using the Pearson correlation test aims to determine the relationship between the two variables. The results showed a correlation between stress levels and blood sugar levels in Diabetes Mellitus patients with pearson correlation analysis obtained p-values of 0.000<0.05 and r = 0.650. The Conclusion there is a relationship between stress levels and blood sugar levels in Diabetes Mellitus patients at the Simpang IV Sipin Health Center in Jambi City. Advice puskesmas to educate patients to better control blood sugar, and encourage patients for always think positively to avoid stressÂ